2021
DOI: 10.3390/universe7070242
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Wavelength Properties of the 2021 Periastron Passage of PSR B1259-63

Abstract: PSR B1259-63 is a gamma-ray binary system hosting a radio pulsar orbiting around a O9.5Ve star, LS 2883, with a period of ∼3.4 years. The interaction of the pulsar wind with the LS 2883 outflow leads to unpulsed broadband emission in the radio, X-ray, GeV, and TeV domains. One of the most unusual features of the system is an outburst of GeV energies around the periastron, during which the energy release substantially exceeds the spin down luminosity under the assumption of the isotropic emission. In this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 37 publications
(28 reference statements)
7
28
0
1
Order By: Relevance
“…If ∆TS > 9, a cutoff is significantly preferred). This is consistent with the results reported in Chernyakova et al [9,14]. Using a power-law with exponentially cut-off model, the spectra index shows significant change between the 2014 and 2017 periastron.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…If ∆TS > 9, a cutoff is significantly preferred). This is consistent with the results reported in Chernyakova et al [9,14]. Using a power-law with exponentially cut-off model, the spectra index shows significant change between the 2014 and 2017 periastron.…”
Section: Resultssupporting
confidence: 92%
“…The main GeV flux peak appeared later and later in the last four periastron passages, as shown in Figure 3, occuring about 90 days after periastron in 2021. This delay pattern is consistent with the trend reported in Chang et al [11], and it is not being observed in any other energy bands [14]. Another feature of the light curves is that there are multiple bright flares during each periastron passage.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations